PENGARUH PENERIMAAN RETRIBUSI PASAR TERHADAP RETRIBUSI DAERAH KABUPATEN BONE BOLANGO - Srihantuti Paramata; Yulin Suleman (Universitas Muhammadiyah Gorontalo, 2022)
The Regional Autonomy Law provides the widest possible opportunity for regions to be able to manage sources of revenue and revenue in order to finance development. The independence of the regions will be reflected in how much the regions depend on the central budget. One of the efforts to encourage regional independence is the issuance of Law Number 28 of 2009 concerning Regional Taxes and Regional Levies. This study aims to determine how the effect of receiving market fees on local fees in Bone Bolango Regency. This study uses a quantitative research approach, namely using simple regression analysis tools. The data source analyzed is secondary data in the form of time-series 2015-2019 time series data. The results show that the market retribution every year in the last 5 years (2015-2019) has continued to decline in terms of realization. This results in a low increase in total local user fees. The results of the calculation of simple linear regeneration and the calculation of the coefficient of determination show that market charges still have a strong influence in encouraging local levies. As can be seen from the results of the calculation and hypothesis testing above, where the RSquarenya value = 0.538 or the magnitude of the influence of market charges on local levies is 53.8% (0.538 x 100). And the remaining 46.2% is influenced by other variables that are not examined.Significant test results on the Summary Model table Sig = 0.01> criteria (0.05), thus the regression equation model based on the research data is not significant, meaning that the linear regression model meets the linearity criteria.